Hidrogeoquímica dos elementos maiores e traço no sistema estuarino Piraquê-Açu e Piraquê-Mirim (Aracruz-ES) - Monteiro, Sury de Moura (2015)
This research aimed to evaluate the dynamic and flow of major elements (Al, Fe and Mn) and trace elements (Cr, Zn, Cu, Cd, Pb, As and Ni) in suspended particulate matter within a tropical estuarine system. This estuarine system comprises two rivers: the Piraquê-açu River (PA) and the Piraquê-mirim River (PM), Espírito Santo, Brazil. The system covers the river basins of PM and PA, with 69.4 km2 and 378.6 km2, respectively. The confluence of these rivers occurs about 4.5 km from the estuary mouth. The PM discharge is five times lower than PA discharge and then the it is dominated by tidal currents during flood tide. The climate is coastal tropical wet-dry type, with two seasonal periods: higher rainfall (200-250mm) and lower rainfall (25-50 mm). Five field works were performed: tree during higher rainfall (March and December, 2013, and March, 2014 ) and two during lower rainfall (June and September, 2013); along spring tide cycle (13 hours); in six sampling stations: two in PA, two in PM and two at these rivers confluence. Sampling of suspended particulate matter (SPM) was performed by water sampling (filtration) and sediment trap; physicochemical and hydrodynamic data were sampled in situ; sedimentological, mineralogical and chemical analysis were conducted in SPM samples; and numerical modelling was applied in order to verify the main transport patterns of these material in scenarios of high and low rainfall. The estuarine system presents alkaline water (pH 7.7±0.8), which is saturated in oxygen (6.17±0.9) with salinity ranging from 25.31±1.5 to 36.92±0.6. PA presented percentages concentration of major elements (16% Al, 10% Fe e 15% Mn) and trace elements (45% Cr, 48% Zn, 56% Cd e 79% Pb) higher than PM, mainly during high rainfall period. Only Ni (55%), Cu (94%) e As (13%) presented higher concentrations in PM. The estuarine confluence reflect the PA influence, during the high rainfall period, when its river discharge carries high concentration of elements for this region; while in the lower rainfall period, there is higher influence of tidal current, when the concentrations of Fe, Mn, Ni e As were highest compared to the both rivers. The geochemical indices indicate that this estuarine system is preserved, and the natural supply is the main source of major and trace elements, which are influenced by the presence of minerals for instance kaolinite, goethite, magnetite, ilmenite, gibbsite, hematite and pyrite. The model scenarios demonstrate the materials transfer (SPM, major and trace elements) between the rivers. The model also shows a greater influence of PA and its confluence on PM, mainly during high rainfall period when there is higher retention of material upstream of PM, that increases the residence time and does it more vulnerable, especially due to accumulation of toxic elements such as Zn and Cr. This estuarine system is materials exporter environment, in which the exportation rate is five times larger in PA than in PM during high rainfall period.